Implementing the Living Qur’an in Building Collective Spirituality through the Tradition of Qur’an Recitation in Islamic Senior High Schools - Nurul Kamilia; Abd. Kahar (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
The focus of this study is the tradition of reciting Surah Al-Waqi’ah and Al-Mulk at MAS Adduriyah Bangkes Kadur Pamekasan, with an analysis of the motivation for implementation and teacher and student perceptions in building students’ collective spirituality. This study is a qualitative field-based research using interactive methods to obtain research results. Data collection was conducted through observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and conclusion. The results show that the implementation of the tradition of reciting the Quran at MAS Adduriyah has a significant and profound impact on school management, especially the formation of students’ ethics and social behavior through repeated interactions with the Quranic verses, thereby creating a spiritual relationship and a school culture that is religious, integrated, and high-quality.